Granulomatous rosacea: a rare atypical variant - Anjana, Vaddarapu; Sirisha, P.; Gopal, K. V. T.; Raju, P. V. Krishnam (International Journal of Research in Dermatology, 2025)
Rosacea is a chronic inflammatory dermatosis mainly affecting the cheeks, nose, chin, and forehead. It is characterized by recurrent episodes of flushing, persistent erythema, phymatous changes, papules, pustules, and telangiectasia. Granulomatous rosacea (GR) is an uncommon variant of rosacea characterized by persistent erythema and papules usually seen in middle age women. Histopathology of GR shows granulomas in upper dermis and has a delayed therapeutic response compared to other types of rosacea. We report an atypical case of GR in a 19-year-old male. A 19-year-old male who presented with reddish dry raised lesions around mouth and nose of 3 months duration. On clinical examination diffuse shiny infiltrated plaques with ill-defined margins were seen over perioral region extending to nasolabial folds, lower forehead including glabellar region. Differential diagnosis of Granulomatous rosacea, Seborrheic dermatitis, Follicular mucinosis, Plaque sarcoidosis was considered. Histopathology showed normal epidermis, interstitial granulomatous infiltrate composed of epithelioid histiocytes, langhans giant cells, lymphocytes suggestive of GR. Patient was treated with oral minocycline 65 mg/day, broad spectrum sunscreen lotion, topical clindamycin gel daily night along with topical ivermectin once weekly resulting in marked clinical improvement after 8 weeks. Classical presentation of GR shows yellowish brown, red papules over cheeks, periorificial regions healing with scar formation. The present case had atypical clinical features presenting with infiltrated and well marginated plaques over multiple facial regions which was confirmed by histopathology and responded satisfactorily to the treatment.